(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
The investigation is part of the author’s line of research: Community Integration, Pedagogy and Evaluation in the training of professionals, with the aim of analyzing the Sentithinking Transphilosophy in universities as an endless prelude, with the use of planetary and complex decolonial transmethods. As part of the complex transmethodology of inquiry and the transmethod of rhizomatic deconstruction, the crisis of colonial philosophy in universities is explored, emphasizing Venezuela and exemplifying the reconstruction in which oppression is subverted with the detachment of the thinking subject, which It is a demonstration of a verb that denies the argument, that challenges with disagreement, well-founded opinions and that leads to understanding a dialectic of the professional that is formed and characterized as part of a training area. Even more delicate is reviewing texts developed by students where the arguments, objectivity, final positions on a subject show that the interpretations are impoverished; we must attend to this with our hands full to give and encourage us to think. For this reason, communities are sentient-thinking agents of the first essence, thus requiring a: teaching commitment in the formation of citizenship from the community pedagogical movement. University students must agree in an environment of understanding of the totality of reality in its parts and in its whole, with depth in Faith, in that reality that God shows him that it can grow or decrease in it. It is an encounter with a multiple way of thinking from where community development and dynamics are thought, the use of laws and shared beliefs that make possible the reunion of their senti-thinking Being of God, for God and in God, absolute dependence. We must decant ourselves from the errors of the colonized philosophy.